DIRECTIONS IN DEVELOPMENT RESEARCH: IDENTITY AS UNIFYING TOOL OF ANALYSIS - Kiguwa, Peace (PINS-Psychology in Society, 2025)
Kalb, D, Pansters, W & Siebers, H (eds) (2004) Globalization and development: Themes and concepts in current research. London: Kluwer Academic Publishers. ISBN 1-4020-2474-6. 190 Pages. Globalization and development: Themes and concepts in current research represent a collective effort from the CERES Research School in development studies in the Netherlands. The key focus of this edited book is a discussion of current themes and concepts that are intertwined with issues of globalization and development research. The six chapters in the book address themselves to broad and specific theoretical and methodological issues of researching economic, political and social development. While the book does maintain easy dialogue throughout, as is perusal with most edited texts, some chapters tend to be more accessible than others.